1966
DOI: 10.1111/j.1440-1754.1966.tb01488.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in Childhood — Some Observations on Precipitating Factors

Abstract: SYNOPSIS The admissions of children with asthma to hospital in Perth, W. Australia during 2 years has been analysed and seasonal trends with associated factors demonstrated: also the usual distribution of patients by year of age is shown. The findings are of a biannual fluctuation in the admission rate of asthmatic children to hospital not associated with significant changes in the clinical infection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1967
1967
1973
1973

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, evidence that there is some relation of asthma to rainfall arises from the relative incidence of asthma in spring and autumn. In Perth the spring wave of asthma was much higher than the autumn wave in each of the 2 years studied (Hobday, 1966); in Perth there is a lush growth of vegetation in spring promoted by retention of moisture in the soil from the heavy winter rains. By contrast in Brisbane, where the autumn wave is the higher, the heavy summer rains produce a lush growth of vegetation in autumn.…”
Section: Relation 1 : Mean Temperatures Under 70"mentioning
confidence: 84%
See 1 more Smart Citation
“…However, evidence that there is some relation of asthma to rainfall arises from the relative incidence of asthma in spring and autumn. In Perth the spring wave of asthma was much higher than the autumn wave in each of the 2 years studied (Hobday, 1966); in Perth there is a lush growth of vegetation in spring promoted by retention of moisture in the soil from the heavy winter rains. By contrast in Brisbane, where the autumn wave is the higher, the heavy summer rains produce a lush growth of vegetation in autumn.…”
Section: Relation 1 : Mean Temperatures Under 70"mentioning
confidence: 84%
“…"Asthma" and "asthmatic bronchitis" were analysed together, as the monthly distribution o€ the 2, as designated in Brisbane, was shown to be the same. A report on asthma (including asthmatic bronchitis) at the Princess Margaret Hospital for Children, Perth, for the years 1962 and 1963 has been published by Hobday (1966). By courtesy of Dr. Hobday, his data have been used in the present analysis, to represent Perth.…”
Section: Asthma Datamentioning
confidence: 99%
“…From his observations on Perth children, Hobday (1966) concluded that the high incidence of asthma in autumn and spring was not associated with increased incidence of respiratory infection. Infection was present in 22% of those admitted in April-June and in 14% of those in October-December.…”
Section: Factors In Generalmentioning
confidence: 99%